Optimization of Human Resource Management in Improving the Quality of Education at MI Hidayatul Islamiyah Pajarakan Probolinggo - Firdausi Achmad; Abdul Hamid; M. Fuad Badruddin (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
School is an educational institution that is responsible for realizing the functions and goals of national education. In this case, the principal has a very strategic role because one of the principal’s duties is to be a manager. The principal must be able to manage the entire school, including managing existing human resources; especially teachers and administrative staff who are direct implementers in school activities who also play a major role in the success of the school in order to achieve the school’s vision, mission and goals. Resource management is carried out through several activities including preparation, arrangement, direction, and supervision. In terms of human resource management, school principals have tasks that are divided into three aspects, including: 1) provision of employees, 2) utilization of existing employees, and 3) building and developing. Factors that support and also hinder human resource management must be managed properly so that good performance will be obtained, school goals can be achieved, and the quality of graduates will increase.